Cost Efficiency Analysis of French Commercial Banks: A Stochastic Frontier Analysis - Ding, Yan (2019)
This research estimated the cost efficiency of 109 French commercial banks between 2011 and 2017 by utilizing the Stochastic Frontier Approach (SFA), and also researched the 8 important factors that have impact on the cost efficiency by using random effect model based on panel data analysis, which includes GDPGR (GDP growth rate), INF (inflation rate), UNE (unemployment rate), EQTA (equity to total assets), SIZE (bank size), NLTA (net loans to total assets) and ROA (return on assets). The main findings are in the following: First, between the year of 2011 and 2017, the cost efficiency of French commercial banks varies from 87.62% to 86.7%. Second, for the determinants, six out of eight determinants that have a significant effect on the bank cost efficiency. To be specific, bank cost efficiency is negatively correlated with SIZE and NPL, while is positively correlated to GDPGR, EQTA, ROA and NLTA.